A practical approach to assessing existing evidence for specific conservation strategies. Issue 4 (21st February 2022) - Salafsky, Nick; Irvine, Robyn; Boshoven, Judy; Lucas, Jaclyn; Prior, Kent; Bisaillon, Jean‐François; Graham, Becky; Harper, Paul; Laurin, André Y.; Lavers, Amanda; Neufeld, Lalenia; Margoluis, Richard
Abstract: There is currently a great deal of work being undertaken to collect, analyze, and synthesize available evidence about the effectiveness of conservation strategies. But substantial challenges still remain in enabling practitioners to assess and apply this evidence to their conservation work in an efficient manner. To solve these challenges, there is growing recognition of the need to use situation assessments and theory of change pathways to detail a set of analytical questions and specific assumptions that can be assessed against the evidence base to "make the case" for a proposed strategy and to identify gaps in knowledge. In this study, we first provide updated definitions of some key terms. We then present and provide examples of an approach to enable practitioners to evaluate the evidence base for the critical assumptions that underlie their specific conservation strategies and to wisely use evidence coming from different knowledge systems. This practical approach, which was developed through a series of pilot tests with Parks Canada projects, involves four iterative steps: (1) identify critical questions and assumptions requiring evidence; (2) assemble and assess the specific and generic evidence for each assumption; (3) determine confidence in evidence and its implications; and (4) validate the assessment and iteratively adapt as needed. Ideally, this approach can be integrated into existing decision‐making frameworks and can also facilitate better cooperation between researchers who synthesize evidence and practitioners who use evidence to make conservation both more effective and efficient.